Control cultural de las malezas en yuca - Leihner, D.E.; Doll, Jerry D. (International Center for Tropical Agriculture, 1979)
Some cultural control measures of weeds in cassava are discussed: quality of the material, planting system and density, density x plant type interaction and use of mulching. In order to study the interaction plant type x planting density, var. M Mex 59 (vigorous) and M Col 22 (nonvigorous) were planted in plots of 7500 and 15,000 plants/ha; and 3 levels of weed control were established: complete, intermediate and no control. The vigorous var. was less than sensitive to a deficiency in control than the nonvigorous var.; the increase in fresh root yield reached up to 60 percent at high densities. Different materials for mulching were evaluated at Carimagua and CIAT (Colombia), obtaining effective weed control with corn husks, hay from Hyparrhenia rufa and Stylosanthes guyanensis, and sugar cane leaves. Moreover, 2 cover crops (Desmodiutn heterophyllum and Phaseolus vulgaris) were evaluated, as well as cane bagasse, chemical control and continuous manual weeding systems. Highest yields in cassava were obtained with weeding 22, 40, 60 and 115 days after planting, but it was the most expensive because of the labor. The 2 cover crops are valid choices for their effectiveness, but their high cost justifies their use only when seed is produced locally and with family labor. Intercropping systems and different weed control practices were studied whereby the stabilizing effect of the cassava yield was verified and the utilization of legumes with short growing cycles was shown to reduce weed growth. It is concluded that there are many possibilities of combining cultural weed control with other measures to permit the farmer to choose between capital or labor input. (CIAT)